Freedom of Expression as a Constitutional Right in Indonesia and Madagascar - Manitra, Ramalina Ranaivo Mikea; Prabandari, Adya Paramita (Jambura Law Review, 2026)
Freedom of expression is a fundamental human right that must be protected. Indonesia and Madagascar have integrated such right into their constitution. However, they still face challenges in implementing it effectively. This paper is a comparative study between Indonesia and Madagascar regarding the legal framework of the right to freedom of expression. The author uses a legal doctrinal method tailored through comparative analysis with secondary data. The study reveals that while both countries constitutionally and internationally commit to protecting freedom of expression, their lower-level legal frameworks such as Indonesia’s ITE Law, and the New Criminal Code, and Madagascar’s Cybercrime Law introduce limitations that may undermine constitutional guarantees. In practice, violations and restrictions persist in both countries, revealing a gap between legal norms and actual enforcement. Nevertheless, from a normative and institutional perspective, each legal system offers lessons for the other. Indonesia’s institutions such as the Press Council, Kominfo, and the Virtual Police, and Madagascar’s ANRCM, CIRGN, and OJM play crucial roles in monitoring and applying these laws, though improvements remain necessary. Notably, Madagascar’s prohibition of government censorship and decriminalisation of press offences through its constitution provide valuable reform insights for Indonesia, whereas Indonesia`s Law No. 39 of 1999 could serve as a model for Madagascar to strengthen the application of its constitutional protection of freedom of expression.